Evaluation of Cell Function Upon Nanovector Internalization. Issue 9 (20th November 2012) - Martinez, Jonathan O.; Parodi, Alessandro; Liu, Xuewu; Kolonin, Mikhail G.; Ferrari, Mauro; Tasciotti, Ennio
<x xml:space="preserve">Abstract</x> In vitro toxicity assays based on the evaluation and retention of advanced and specific cellular functions are proposed to investigate mesoporous silicon nanovectors. This approach provides greater insight compared to simple cellular viability and toxicity assays. Electron microscopy images demonstrate internalized nanovectors altering the curvature of the nuclear envelope with minimal effect on viability or biological function. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>